In vitro disappearance characteristics of selected categories of commercially available dog treats*. (10th October 2014) - de Godoy, Maria R. C.; Vermillion, Ryan; Bauer, Laura L.; Yamka, Ryan; Frantz, Nolan; Jia, Tim; Fahey, George C.; Swanson, Kelly S.
Abstract: Pet owners desire treats with adequate nutritional profiles, functional benefits, long-lasting properties and an interactive nature. Therefore, it is pivotal to understand the digestion characteristics of treats produced by different processing methods and having variable nutritional composition. The objective of the present study was to measure in vitro disappearance characteristics of selected categories of commercially available treats. In vitro procedures developed by Boisen and Eggum in 1991 were modified to handle larger sample sizes. Treat samples were evaluated in triplicate. Following incubation, in vitro DM disappearance (DMD) was calculated. In vitro DMD of selected treats varied widely. For the gastric phase, DMD ranged from 6·9 to 88·8 %, whereas intestinal phase digestion resulted in a DMD range of 10·7–100·0 % ( P  < 0·05). Because of differences in treat composition and size, they were divided into six categories: Biscuit, Bone, Chew, Dental, Meat Product and Rawhide. In general, Bone was the least digestible treat category in both gastric and intestinal phases. Meat Product and Rawhide treats had a DMD of 71·5–100 % after the intestinal phase, whereas Biscuit had values above 93 %. Chew and Dental treats had a wide DMD range (54·5–100 %). Understanding the DMD of commercially available treats is important to verify their safety for consumption and potential digestibility once ingested. These data indicate wide variation in DMD among and within different treat categories. This information will assist pet food sale associates, pet owners and veterinarians to make more educated decisions when it relates to selection and recommendations about commercially available treats. Future work is needed to expand the knowledge on in vitro DMD and safety of treats and to further investigate their impact on in vivo DM digestibility once fed to dogs.